Application of Endoscopy in Improving Survival of Cirrhotic Patients with Acute Variceal Hemorrhage - Yao-Chun Hsu; Chen-Shuan Chung; Hsiu-Po Wang (International Journal of Hepatology)
Playing a central role in the modern multidisciplinary management of acute gastroesophageal variceal hemorrhage, endoscopy is essential to stratify patient at risk, control active hemorrhage, and prevent first as well as recurrent bleeding. Before endoscopic procedure, antibiotic prophylaxis along with vasoactive medication is now routine practice. Intravenous erythromycin effectively cleanses stomach and may improve the quality of endoscopy. The timing of endoscopy should be on an urgent basis as delay for more than 15 hours after presentation is associated with mortality. Active variceal bleeding on endoscopy in a patient with hepatic decompensation heralds poor prognosis and mandates consideration of aggressive strategy with early portosystemic shunting. Band ligation has become the preferred modality to control and prevent bleeding from esophageal varices, although occasionally sclerotherapy may still be used to achieve hemostasis. Addition of pharmacotherapy with nonselective beta blockade to endoscopic ligation has become the current standard of care in the setting of secondary prophylaxis but remains controversial with inconsistent data for the purpose of primary prophylaxis. Gastric varices extending from esophagus may be treated like esophageal varices, whereas variceal obliteration by tissue glue is the endoscopic therapy of choice to control and prevent bleeding from fundic and isolated gastric varices.